Sipuncula (Peanut Worms) in Indonesia Waters: A Review - Cintra, Allsay Kitsash Addifisyukha; Fitrian, Tyani; Novianty, Hilda; Jasmadi, Jasmadi; Sjafrie, Nurul Dhewani Mirah (Marine Science Department Diponegoro University, 2024)
Sipunculans, or peanut worms, are unsegmented worm-like marine organisms with distinctive trunk-like bodies. They play important roles in marine ecosystems, such as bioerosion, bioturbation, and food sources. Sipunculans are also harvested as human food in some regions worldwide. Despite their importance, a comprehensive understanding of the Sipuncula in Indonesia is still limited. This work aimed to compile a study of the distribution, ecology, and potency of Sipuncula species in Indonesian waters. The distribution of Sipuncula species in Indonesian waters was recorded from the northernmost to the easternmost part of Indonesia. So far, nineteen species have been found in Indonesian waters and are dominated by Sipunculus nudus. In Indonesia, Sipuncula exhibits a diverse range of habitats, they can be found in seagrass, mangrove and coral reef ecosystems, in both sandy and muddy sediments. Sipunculans found in Indonesia have ecosystem function as bioturbator, shell-utilizer, and coral-symbiotic species. Sipuncula also has potency as a food and nutraceutical for human health maintenance because it contains highly nutritious such as protein, carbohydrates, ash, lipids, moisture, minerals, amino acids, and fatty acids. In some areas in Indonesia, local communities use Sipuncula as a traditional food source and fishing bait. Given its significance for marine ecosystems and human livelihoods in Indonesia, future management strategies should include regulations on catch size and management practices, data collection, promotion of sustainable fishing practices, and research on Sipuncula biology and ecology. Addressing these knowledge gaps will help to ensure the sustainable use and conservation of Sipuncula in Indonesia.